Sleep in the dog: comparative, behavioral and translational relevance. (June 2020) - Bódizs, Róbert; Kis, Anna; Gácsi, Márta; Topál, József
Highlights: All behavioral and polygraphic criteria of (NREM and REM) sleep are met in the dog. Dogs are diurnal: weak circadian modulation and assumed adaptation to human rhythms. Pre-sleep experiences, location and socio-ecological factors affect canine sleep. Sleep may contribute to dogs' memory consolidation. Development and aging affect sleep and cognition in dogs. Abstract : The dog (Canis familiaris) is a promising non-invasive translational model of human cognitive neuroscience including sleep research. Studies on the relationship between sleep and cognition in dogs and other canines are only just emerging, but still very scarce. Here we provide insight into canine sleep and sleep-related physiological and cognitive/behavioral phenomena. We show that dogs do not only fulfil all behavioral and polygraphic criteria of sleep, but are characterized by sleep homeostasis, diurnal pattern of activity, circadian rhythms, ultradian sleep cycles, socio-ecologically and environmentally shaped wake-sleep structure, sleep-related memory improvement, as well as specific sleep disorders. Developmental patterns of sleep-related physiological indices, as well as parallel trends in age-dependent changes in cognition and sleep were evidenced in dogs.